2020
DOI: 10.1039/d0ew00777c
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of bacterial bioaugmentation for groundwater Mn removal using a waste-based culture medium and lyophilization

Abstract: Waste based bacterial culture media and inoculum lyophilization to optimize bioaugmentation processes applicable to Mn groundwater full-scale biofiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Sand inoculated with MOB-513-pBdcB fresh cultures or lyophiles, both grown in Lept or Lept-Mn, showed a higher Mn(II) oxidation capacity than those inoculated with MOB-513-pEmpty (Table 2). On the other hand, and as previously observed (10), bacterial adaptation to Mn(II) performed by growing the strains in Lept-Mn enhanced the oxidation of Mn(II) present in groundwater (Table 2). No BMnOx was detected for MOB-513-pBpdeA at the assayed timepoints (Table 2).…”
Section: Overexpression Of Bdcb In Mob-513 Improves Lyophilisation An...supporting
confidence: 85%
See 4 more Smart Citations
“…Sand inoculated with MOB-513-pBdcB fresh cultures or lyophiles, both grown in Lept or Lept-Mn, showed a higher Mn(II) oxidation capacity than those inoculated with MOB-513-pEmpty (Table 2). On the other hand, and as previously observed (10), bacterial adaptation to Mn(II) performed by growing the strains in Lept-Mn enhanced the oxidation of Mn(II) present in groundwater (Table 2). No BMnOx was detected for MOB-513-pBpdeA at the assayed timepoints (Table 2).…”
Section: Overexpression Of Bdcb In Mob-513 Improves Lyophilisation An...supporting
confidence: 85%
“…Previous studies showed the usefulness of MOB lyophilised cultures to replace large volumes of inoculum and to enhance groundwater Mn removal performance (10). Since MOB-513-pBdcB shows a higher biofilm formation capacity and is a hyper-oxidant bacterial strain, we expanded our analysis to consider the biotechnological relevance of c-di-GMP function in MOB-513.…”
Section: Overexpression Of Bdcb In Mob-513 Improves Lyophilisation An...mentioning
confidence: 99%
See 3 more Smart Citations